ANALISIS PEMANFAATAN DANA KAPITASI OLEH PUSKESMAS DALAM PENYELENGGARAAN JAMINAN KESEHATAN NASIONAL DI KABUPATEN PURBALINGGA - Risa Tri Anggraeni; Ayun Sriatmi; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2016)
National Health Insurance program is a part of National Social Insurance System that organized to provide protection assurance and social welfare for all the people of Indonesia based on act number 40 of 2004.The primary health care as means of basic health services receive BPJS funds in capitation fom based on the number of participants of National Health Insurance who registered in the working area of the primary health care. Purbalingga regency with the registered participants percentage of 68,98% from total population receive the primary health care capitation funds with total amounting of Rp37.141.230.500,00 and 90% utilization rate. This research aim is to analyze the utilization of capitation funds for health services, operational costs support, as well as promotive and preventive effort by primary health care in Purbalingga regency. This research is a qualitative research with indepth interviews and observations method on the Treasurer of National Health Insurance in primary health care. Results showed that the allocation of health care services and support of the operational costs in Purbalingga regency has the same allocation rules with Permenkes number 19 of 2014. However, not all public health centers allocates in the same way characterized by the allocation of services of 60% in only one public health center. Dissatisfaction on the sharing of service charge is caused by calculation of the points on the variable components of education, years of service, and attendance. Meanwhile, all primary health care in Purbalingga doesn’t allocate the same thing for the support of operational costs in accordance with the rules set. There are waiting time required by primary health care for procurement support of operational costs by using e-catalogs. On the utilization of preventive promotive there are 4 of 7 primary health care which not allocated capitation funds for promotive and preventive efforts.To overcome this, it takes the role of leader to improve the utilization of capitation funds in accordance with the needs of the primary health care.